An Aging Population of Chronic Hepatitis B With Increasing Comorbidities: A Territory‐Wide Study From 2000 to 2017 - Wong, Grace Lai‐Hung; Wong, Vincent Wai‐Sun; Yuen, Becky Wing‐Yan; Tse, Yee‐Kit; Luk, Hester Wing‐Sum; Yip, Terry Cheuk‐Fung; Hui, Vicki Wing‐Ki; Liang, Lilian Yan; Lui, Grace Chung‐Yan; Chan, Henry Lik‐Yuen (Hepatology (Baltimore, Md.), 2020)
Patients with chronic hepatitis B (CHB) are aging because of improved survival under better health care. This has an important implication on the choice of antiviral treatment (AVT), given that long‐term safety would be a concern in the presence of multiple comorbidities. We aimed to determine the prevalence of key comorbidities and concomitant medications in a territory‐wide CHB cohort in Hong Kong in 2000‐2017. CHB patients who have been under the care at primary, secondary, and tertiary medical centers in the public sector were identified through the Clinical Data Analysis and Reporting System of the Hospital Authority, Hong Kong. The demographics and prevalence of key comorbidities, including diabetes mellitus, hypertension, chronic kidney disease, osteopenia/osteoporosis based on diagnosis codes, relevant medications, and/or laboratory parameters, were determined according to CHB patients’ first appearance in four time periods: 2000‐2004, 2005‐2009, 2010‐2013, and 2014‐2017. In the final analysis, 135,395 CHB patients were included; the mean age increased with time: 41 ± 15 years in 2000‐2004; 46 ± 17 years in 2005‐2009; 51 ± 16 years in 2010‐2013; and 55 ± 15 years in 2014‐2017. There was a trend of increasing prevalence of several common comorbidities over the four periods: hypertension 25.5%, 23.8%, 27.2%, and 28.6%; diabetes mellitus 10.6%, 12.5%, 16.1%, and 20.1%; cardiovascular disease 12.5%, 16.9%, 20.9%, and 22.2%; and malignancy 7.0%, 13.2%, 17.3%, and 23.6%, respectively (all P < 0.001). Conclusion: CHB patients are getting older with increasing prevalence of common comorbidities. These comorbidities should be taken into account when choosing AVT.